Biasplot: A Package to Effective Plots to Assess Bias and Precision in Method Comparison Studies. (March 2017) - Taffé, Patrick; Peng, Mingkai; Stagg, Vicki; Williamson, Tyler
Bland and Altman's (1986, Lancet 327: 307–310) limits of agreement have been used in many clinical research settings to assess agreement between two methods of measuring a quantitative characteristic. However, when the variances of the measurement errors of the two methods differ, limits of agreement can be misleading.biasplot implements a new statistical methodology that Taffé (Forthcoming, Statistical Methods in Medical Research ) recently developed to circumvent this issue and assess bias and precision of the two measurement methods (one is the reference standard, and the other is the new measurement method to be evaluated).biasplot produces three new plots introduced by Taffé: the "bias plot", "precision plot", and "comparison plot". These help the investigator visually evaluate the performance of the new measurement method. In this article, we introduce the user-written command biasplot and present worked examples using simulated data included with the package. Note that the Taffé method assumes there are several measurements from the reference standard and possibly as few as one measurement from the new method for each individual.